(untitled) (Research, Society and Development, 2020)
Objective: To report the experience of the 1st Symposium on Health Invisibilities of the LGBT+ (Lesbians, Gays, Bisexuals and Transgenders) community, its reflections and implications for medical education. Methodology: This is a descriptive study of an experience report about a symposium held at the State University of Rio de Janeiro (UERJ), carried out by six members of the Humanities Department of the academic center of the medical course, on “Invisibilities in LGBT+ Community Health”. For the evaluation of the curriculum, a semi-structured questionnaire was applied to the students of the institution, which demonstrated the little LGBT + approach in medical training. Conversation circles were then developed to discuss the vulnerabilities of this community with academics, as a means of acquiring knowledge on the topic. With this, broad subjects of discussion arose that fostered the creation of the symposium as a teaching-learning method. Results: This event consisted of two tables: (1) Invisibilities and Silences of the LGBT+ Community, discussing social issues and the construction of being a doctor for the LGBT + medical student and (2) LGBT+ Community and the Right to Health, which included the health challenges experienced by the LGBT+ community. Comprehensive topics were discussed by a multiprofessional team of LGBT+ specialists and students, promoting knowledge for students and the external community, bringing also reflection to the institution’s coordinators on the approach to LGBT+ content in the curriculum. Conclusion: The symposium stood out as a powerful pedagogical strategy allowing students to get in touch with the specificities of LGBT+ populations and opened the way for addressing the theme in medical education.